Preparation of carbon nanomaterials and their application in water purification - Xu, Z (2023)
Water contamination is a severe problem faced by the whole world. With the rapid growth in global population, this problem is even worsening. Fullerene and TiO2 are promising photocatalysts for water purification owing to their intrinsically high photocatalytic activity. Yet, a lot of weaknesses (e.g. large bandgap of TiO2, hydrophobicity of fullerene, etc.) unfortunately inhibit them from fulfilling their potential in water purification. In this thesis, different strategies were designed to synthesize and functionalize various carbon nanomaterials. Afterwards, these specifically designed and prepared carbon nanomaterials were employed to overcome the intrinsic weaknesses of both fullerene and TiO2. Great improvement in photodynamic performance was witnessed in both photocatalysts. Their potential in water purification was hence proved.